68.7k views
1 vote
Given g(x) where f(x)= 3x-1 and g(x)= f(x+1). graph

User GusSL
by
5.2k points

1 Answer

1 vote

Answer:

The graph in the attached figure

Explanation:

we have


f(x)=3x-1

we know that

To find out the function f(x+1) exchange the variable x for (x+1) in the function f(x)

so


f(x+1)=3(x+1)-1


f(x+1)=3x+3-1


f(x+1)=3x+2

therefore


g(x)=3x+2

using a graphing tool

see the attached figure

Given g(x) where f(x)= 3x-1 and g(x)= f(x+1). graph-example-1
User OscarVGG
by
5.0k points